Variable characteristics of viscosity and thermal conductivity in peristalsis of magneto-Carreau nanoliquid with heat transfer irreversibilities. (July 2020) - Khan, W.A.; Farooq, S.; Kadry, S.; Hanif, M.; Iftikhar, F.J.; Abbas, S.Z.
Highlights: Carreau nanomaterial flow with entropy aspect is studied. Viscous dissipation and nonlinear porous medium attributes are accounted. Mass transfer together with chemical reaction and activation energy is modeled. Numeric solutions are constructed via built-in shooting algorithm. Abstract: Background: : Peristaltic is a basic way of fluid transportation in physiology, engineering and nuclear industry. Importance of peristalsis is due to its contraction and compulsion property of symmetric and asymmetric type channel walls. Another beauty of this mechanism is that the channel walls propagates and push the material along the tube/conduit channel walls. This mechanism shows its presence in physiology while food particles are transferred through esophagus and stomach, urine through intestines, spermatoza transportation in reproductive tract. In industry it is found in roller and finger pumps, drug delivery and various nuclear materials e.g. toxic, corrosive, noxious etc. Magnetic field in peristalsis is found helpful in treatment of various treatments using magnets. Actually earth and human body as a whole comprises of magnetic and electric fields. The medical specialists found that unbalances of electromagnetic field in human body is the reason for emotional and physical disturbance. In addition it has significant and potential utilizations in modification of medical, industrial and chemical, procedures for example MRI, evaporation, convection, thermoregulation, MHD throttles, and in various types of tumor treatments. Entropy production work out irreversibility in complex systems which are frequently encountered in industrial mechanisms. In view of that, this methodology is effectually implemented in distinct technological applications covering porous media, propulsion ducts, electronic cooling, turbo-machinery and combustion. Method: : Modelled flow mechanism is nonlinear and coupled due to considered assumptions (i.e. nanofluid, nonlinear porous channel, mixed convection, variable viscosity and thermal conductivity, activation energy and chemical reaction). Such nonlinear and coupled system is difficult to tackle analytically. Thus to obtain the solution we employed RK algorithm for numerical simulations. Results: : Stronger magnetic parameter shows resistive characteristics to the flow field. Nonlinear Darcy medium assists the fluid motion at channel center and resits at walls vicinity. Variable characteristics of thermal conductivity moderate the soak or disperse up heat ability which corresponds to temperature reduction. Thermal slip quantity increase the temperature whereas concentration slip deduct the concentration of Carreau nanomaterial. Entropy and Bejan number shows maximum response for higher dissipation estimations. Brownian and thermopherotic motions aspects has reverse impact on nanomaterial concentration. Conclusion: : Entropy and Bejan number deduces for higher variable thermal conductivity values. Carreau material variable enhance the entropy of the system as a whole.